2022
DOI: 10.5009/gnl210369
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Potential Gut Microbiota-Derived Biomarkers to Predict the Success of Fecal Microbiota Transplantation in Ulcerative Colitis: A Prospective Cohort in Korea

Abstract: Background/Aims: Although fecal microbiota transplantation (FMT) has been proven as one of the promising treatments for patients with ulcerative colitis (UC), potential prognostic markers regarding the clinical outcomes of FMT remain elusive. Methods:We collected fecal samples of 10 participants undergoing FMT to treat UC and those from the corresponding donors. We categorized them into two groups: responders and nonresponders. Sequencing of the bacterial 16S rRNA gene was conducted on the samples to explore b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…These findings are consistent with previous studies that also reported remarkable success rates after FMT. (17,18,19,20,21,22,23,24,25) In addition, the review highlights the importance of specific microbial composition in the resolution of rCDI. Patients who responded to treatment showed an increase in the abundance of several bacterial families, such as Ruminococcaceae, Prevotellaceae, and Bacteroidaceae, along with a decrease in Enterobacteriaceae.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with previous studies that also reported remarkable success rates after FMT. (17,18,19,20,21,22,23,24,25) In addition, the review highlights the importance of specific microbial composition in the resolution of rCDI. Patients who responded to treatment showed an increase in the abundance of several bacterial families, such as Ruminococcaceae, Prevotellaceae, and Bacteroidaceae, along with a decrease in Enterobacteriaceae.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteroides caccae promotes mucus degradation, which reduces intestinal inflammation by decreasing bacterial interactions with epithelial cells in the large intestine. In addition, Colidextribacter abundance is significantly correlated with pro-inflammatory metabolites generated by the gut microbiome, suggesting that Colidextribacter could produce inflammatory metabolites [ 54 ]. We also identified that Bifidobacterium pseudolongum abundance was significantly higher in the HY7302H-treated DE group than in the untreated DE group ( p = 0.033).…”
Section: Discussionmentioning
confidence: 99%